TATA CARA ROOM ATTENDANT DALAM USAHA MENJAGA KUALITAS KEBERSIHAN KAMAR KING SUITE DI HARD ROCK HOTEL BALI - RADITYA, I PUTU TIANA RADITYA; Wisnawa, I Made Bayu; Antara, I Made Agung Rai (HARMONY HOSPITALITY, 2022)
Hard Rock Hotel Bali is a 5 star hotel located in Kuta. To provide maximum service quality, it is very important to pay attention to the quality of room cleanliness especially the King Suite Room, which in general should pay more attention to the cleanliness of the room. As one of the best rooms in Hard Rock, the quality of cleanliness in the King Suite Room really nees to be considered in order to minimize guest complaints and provide the best experience in the best Hard Rock rooms. In the current pandemic situation with very spacious room conditions, standard room cleaning procedures must pay more attention to guest comfort according to the protocol in order to maintain in health of the both guests ans staff who clean the room, therefore the author raises the title Prosedure for Room Attendent in a effort to maintain cleanliness quality King Suite Room at Hard Rock Hotel Bali. The theoretical basis for writing this final report includes procedures, housekeeping, business, quality, cleanliness, rooms. Data collection techniques used are observation, interviews, and documentation. The result of this study are that the Room Attendant must follow the procedures for cleaning the King Suite Room in an effort to maintain the quality of room cleanliness at Hard Rock Hotel Bali to comply with the procedures established in accordance with the current pandemic situation.